Familial Aggregation of Systemic Lupus Erythematosus, Rheumatoid Arthritis, and Other Autoimmune Diseases in 1177 Lupus Patients From the GLADEL Cohort (2005)
ABSTRACT: Objective. To determine whether there is familialaggregation of systemic lupus erythematosus (SLE)and/or other autoimmune diseases in SLE patients andto identify clinical differences between patients with andthose without familial autoimmunity.Methods. We interviewed members of the GrupoLatinoamericano de Estudio del Lupus Eritematoso(GLADEL) inception cohort of 1,214 SLE patients toascertain whether they had relatives with SLE and/orother autoimmune diseases. Identified relatives werestudied. Familial aggregation was tested using reportedhighest and intermediate population prevalence datafor SLE, rheumatoid arthritis (RA), or all autoimmunediseases, and studies were performed to identify thegenetic model applicable for SLE.Results. We identified 116 first-, second-, or third-degree relatives with SLE, 79 with RA, 23 with auto-immune thyroiditis, 3 with scleroderma, 1 with polymy-ositis, and 16 with other autoimmune diseases, relatedto 166 of the 1,177 SLE patients in the GLADEL cohortwho agreed to participate. Forty-two SLE patients had 2 r more relatives with an autoimmune disease. Wefound a␭siblingof 5.8 and 29.0 for SLE and of 3.2–5.3 forRA, when comparing with their reported high or inter-mediate population prevalence, respectively. We alsofound familial aggregation for autoimmune disease ingeneral (␭siblingⴝ 1.5) and determined that for SLE, apolygenic additive genetic model, rather than a multi-plicative one, is applicable.Conclusion. In SLE there is familial aggregationof SLE, RA, and autoimmune disease in general. Apolygenic additive model applies for SLE. AmericanIndian–white Mestizo SLE patients and those withhigher socioeconomic level were more likely to havefamilial autoimmunity